1990
DOI: 10.1007/bf00023370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light intensity and quality on the growth rate and photosynthetic pigment content of Spirulina platensis

Abstract: The quantitative and qualitative effects of light on carotenoid production by Spirulina were studied. Maximum total carotenoid production was measured in cells grown under white light at an irradiance of 432 pmol photon m-2 s -, the onset of light saturation for this organism as determined by growth rates. A true maximum may exist at irradiances above 1500 mol photon m -2 s-t under white light.Individual carotenoids responded differently to light conditions. Under white light, fB-carotene and echinenone were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 35 publications
(26 reference statements)
6
25
0
4
Order By: Relevance
“…In particular, the p-carotene increase in L1 grown cultures, quite comparable with that observed both in 0 . agardhii (Millie et al 1990) and in Spirulina platensis (Olaizola & Duerr 1990), is in agreement with a light-harvesting or structural role of this pigment in the photosystem I (Olaizola & Duerr 1990). Therefore, our results indicate that in the strain 3F carotenoids may serve as an accessory pigment and for photoprotection.…”
Section: -supporting
confidence: 90%
“…In particular, the p-carotene increase in L1 grown cultures, quite comparable with that observed both in 0 . agardhii (Millie et al 1990) and in Spirulina platensis (Olaizola & Duerr 1990), is in agreement with a light-harvesting or structural role of this pigment in the photosystem I (Olaizola & Duerr 1990). Therefore, our results indicate that in the strain 3F carotenoids may serve as an accessory pigment and for photoprotection.…”
Section: -supporting
confidence: 90%
“…This indicates that C. officinalis can be photoacclimated to high light intensities by changing photosynthetic pigment content to optimize photosynthetic rate. carotenoids content of C. officinalis also increased at low light, as in the green alga Spirulina platensis (Olaizola and Duerr 1990). This supports the hypotheses that carotenoids are closely associated with chlorophyll a content, that they increase at low light intensity, and that they serve as light harvesting pigments or a structural component of photosystem I (Olaizola and Duerr 1990).…”
Section: Discussionsupporting
confidence: 76%
“…A linear relationship was found between growth rates and light intensity (Figure 8), except for the first point at 85 µmol/m 2 /s. Light saturation could not be reached at 430 µmol/m 2 /s, while some studies found photoinhibition around 300 µmol/m 2 /s [29] or 432 µmol/m 2 /s [30]. These differences might be explained by different Spirulina strain and different lighting conditions.…”
Section: Effect Of Light Intensity On Spirulina Growthmentioning
confidence: 88%